Improving marine heatwave statistics in global climate models using machine learning: a case study for the north–west European Shelf - Johannes Becherer; Thomas Pohlmann (Climate Dynamics, 2026)
The investigation of future marine heatwave (MHW) trends in a changing climate is seriously hindered by the inability of current-generation global climate models (GCMs) to accurately reproduce high-frequency sea surface temperature (SST) variations. This limitation of GCMs is due to their coarse resolution and lack of parameterization for important small-scale processes. In this study, we introduce a novel hybrid model that combines low-frequency GCM simulation data with a machine learning (ML) component to incorporate realistic high-frequency SST variations. The ML model component is trained on 42 years of historical ERA5-reanalysis data. The hybrid model serves as a computationally inexpensive add-on to incorporate realistic high-frequency SST variability into existing GCM ensemble simulations or other low-frequency SST products. We demonstrate that the hybrid model yields MHW statistics that more closely align with past observations compared to data derived solely from MPI-ESM1.2-LR, a commonly used GCM. In particular, the well-known bias of GCMs towards longer and less frequent MHWs vanishes entirely in the hybrid model. We then utilize the hybrid model to examine the temporal evolution of MHW statistics on the North-West European Shelf (NWES) from 1850 to 2100, across multiple state-of-the-art CMIP6 scenarios. MHW statistics are projected to saturate in the future, leading to a counterintuitive decrease in event frequency. A return period analysis reveals that extremely long-lasting MHWs are expected to become 100 times more likely by the end of the century, with cumulative intensities reaching levels that were virtually impossible during pre-industrial times.

The impact of mean sea level rise on the oceanic water exchange of a back-reef lagoon - Jian Su; Bernhard Mayer; Xinping Chen; Thomas Pohlmann (Regional Studies in Marine Science, 2024)

Long-term changes of cross-shelf transports in the Yellow and East China Seas under different greenhouse gases emission scenarios - Jiajia Hao; Dongliang Yuan; Di Tian; Jian Su; Thomas Pohlmann (Climate Dynamics, 2022)

Chasing the offshore wind farm wind-wake-induced upwelling/downwelling dipole - Jens Floeter; Thomas Pohlmann; André Harmer; Christian Möllmann (Frontiers in Marine Science, 2022)
The operational principle of offshore wind farms (OWF) is to extract kinetic energy from the atmosphere and convert it into electricity. Consequently, a region of reduced wind speed in the shadow zone of an OWF, the so-called wind-wake, is generated. As there is a horizontal wind speed deficit between the wind-wake and the undisturbed neighboring regions, the locally reduced surface stress results in an adjusted Ekman transport. Subsequently, the creation of a dipole pattern in sea surface elevation induces corresponding anomalies in the vertical water velocities. The dynamics of these OWF wind-wake induced upwelling/downwelling dipoles have been analyzed in earlier model studies, and strong impacts on stratified pelagic ecosystems have been predicted. Here we provide for the first time empirical evidence of the existence of such upwelling/downwelling dipoles. The data were obtained by towing a remotely operated vehicle (TRIAXUS ROTV) through leeward regions of operational OWFs in the summer stratified North Sea. The undulating TRIAXUS transects provided high-resolution CTD data which enabled the characterization of three different phases of the ephemeral life cycle of a wind-wake-induced upwelling/downwelling dipole: development, operation, and erosion. We identified two characteristic hydrographic signatures of OWF-induced dipoles: distinct changes in mixed layer depth and potential energy anomaly over a distance < 5 km and a diagonal excursion of the thermocline of ~10–14 m over a dipole dimension of ~10–12 km. Whether these anthropogenically induced abrupt changes are significantly different from the corridor of natural variability awaits further investigations.

The Impact of Fortnightly Stratification Variability on the Generation of Baroclinic Tides in the Luzon Strait - Zheen Zhang; Xueen Chen; Thomas Pohlmann (Journal of Marine Science and Engineering, 2021)
The impact of fortnightly stratification variability induced by tide–topography interaction on the generation of baroclinic tides in the Luzon Strait is numerically investigated using the MIT general circulation model. The simulation shows that advection of buoyancy by baroclinic flows results in daily oscillations and a fortnightly variability in the stratification at the main generation site of internal tides. As the stratification for the whole Luzon Strait is periodically redistributed by these flows, the energy analysis indicates that the fortnightly stratification variability can significantly affect the energy transfer between barotropic and baroclinic tides. Due to this effect on stratification variability by the baroclinic flows, the phases of baroclinic potential energy variability do not match the phase of barotropic forcing in the fortnight time scale. This phenomenon leads to the fact that the maximum baroclinic tides may not be generated during the maximum barotropic forcing. Therefore, a significant impact of stratification variability on the generation of baroclinic tides is demonstrated by our modeling study, which suggests a lead–lag relation between barotropic tidal forcing and maximum baroclinic response in the Luzon Strait within the fortnightly tidal cycle.

Correlation between subsurface salinity anomalies in the Bay of Bengal and the Indian Ocean Dipole and governing mechanisms - Zheen Zhang; Thomas Pohlmann; Xueen Chen (Ocean Science, 2021)
Lead–lag correlations between the subsurface temperature and salinity anomalies in the Bay of Bengal (BoB) and the Indian Ocean Dipole (IOD) are revealed in model results, ocean synthesis, and observations. Mechanisms for such correlations are further investigated using the Hamburg Shelf Ocean Model (HAMSOM), mainly relating to the salinity variability. It is found that the subsurface salinity anomaly of the BoB positively correlates to the IOD, with a lag of 3 months on average, while the subsurface temperature anomaly correlates negatively. The model results suggest the remote forcing from the equatorial Indian Ocean dominates the interannual subsurface salinity variability in the BoB. The coastal Kelvin waves carry signals of positive (negative) salinity anomalies from the eastern equatorial Indian Ocean and propagate counterclockwise along the coasts of the BoB during positive (negative) IOD events. Subsequently, westward Rossby waves propagate these signals to the basin at a relatively slow speed, which causes a considerable delay of the subsurface salinity anomalies in the correlation. By analyzing the salinity budget of the BoB, it is found that diffusion dominates the salinity changes near the surface, while advection dominates the subsurface; the vertical advection of salinity contributes positively to this correlation, while the horizontal advection contributes negatively. These results suggest that the IOD plays a crucial role in the interannual subsurface salinity variability in the BoB.

Possible impacts of anthropogenic climate change to the upwelling in the South Brazil Bight - Mihael Machado de Souza; Moritz Mathis; Bernhard Mayer; Maurício Almeida Noernberg; Thomas Pohlmann (Climate Dynamics, 2020)
Anthropogenic climate change is expected to strengthen upwelling events worldwide, driven by an increase of upwelling-favorable winds. However, Earth System Models (ESM) tend to underestimate regional processes due to their coarse grid resolution, which can lead to local biases. We use a high-resolution ocean model ( $${1/12}^{° }$$ 1 / 12 ∘ ) forced by results from the Max-Planck-Institute-ESM to analyze the impact of the RCP8.5 emission scenario on the upwelling of South Atlantic Central Water (SACW) in the South Brazil Bight (SBB). We find a stronger Ekman forcing and a higher spread of SACW over the shelf, but this does not translate into higher vertical velocities at the bottom of the mixed-layer in the end of the century. The increased winds’ effect is essentially balanced by an increase in water column stability due to the surface warming. This is particularly important during austral summer, when this process tends to weaken the upwelling. Vertical velocities decrease significantly along the shelf break. Here, the upwelling regime is governed by the Brazil Current (BC) and slight changes in transport induce large responses in upwelling strength. The consequences are increased sea surface temperatures over most of the shelf, although mitigated by the SACW upwelling and kept below global projections. However, temperatures decrease along Cabo Frio. In this region, shelf break upwelling dominates and is enhanced by a local increase in the BC transport. This highlights the importance of regional processes and, more specifically, of changes in the BC transport for the upwelling in the SBB.

Driving mechanisms of the variability and long-term trend of the Brazil–Malvinas confluence during the 21st century - Mihael M. de Souza; Moritz Mathis; Thomas Pohlmann (Climate Dynamics, 2019)

The Spatial and Temporal Variability of Air-Sea CO2 Fluxes and the Effect of Net Coral Reef Calcification in the Indonesian Seas: A Numerical Sensitivity Study - Bernhard Mayer; Tim Rixen; Thomas Pohlmann (Frontiers in Marine Science, 2018)

A Novel Modeling Approach to Quantify the Influence of Nitrogen Inputs on the Oxygen Dynamics of the North Sea - Fabian Große; Markus Kreus; Hermann-Josef Lenhart; Johannes Pätsch; Thomas Pohlmann (Frontiers in Marine Science, 2017)

Synoptic fluctuation of the Taiwan Warm Current in winter on the East China Sea shelf - Jiliang Xuan; Daji Huang; Thomas Pohlmann; Jian Su; Bernhard Mayer; Ruibin Ding; Feng Zhou (Ocean Science, 2017)
The seasonal mean and synoptic fluctuation of the wintertime Taiwan Warm Current (TWC) were investigated using a well-validated finite volume community ocean model. The spatial distribution and dynamics of the synoptic fluctuation were highlighted. The seasonal mean of the wintertime TWC has two branches: an inshore branch between the 30 and 100 m isobaths and an offshore branch between the 100 and 200 m isobaths. The Coriolis term is much larger than the inertia term and is almost balanced by the pressure gradient term in both branches, indicating geostrophic balance of the mean current. Two areas with significant fluctuations of the TWC were identified during wintertime. One of the areas is located to the north of Taiwan with velocities varying in the cross-shore direction. These significant cross-shore fluctuations are driven by barotropic pressure gradients associated with the intrusion of the Taiwan Strait Current (TSC). When a strong TSC intrudes to the north of Taiwan, the isobaric slope tilts downward from south to north, leading to a cross-shore current from the coastal area to the offshore area. When the TSC intrusion is weak, the cross-shore current to the north of Taiwan is directed from offshore to inshore. The other area of significant fluctuation is located in the inshore area between the 30 and 100 m isobaths. The fluctuations are generally strong both in the alongshore and cross-shore directions, in particular at the latitudes 26.5 and 28° N. Wind affects the synoptic fluctuation through episodic events. When the northeasterly monsoon prevails, the southwestward Zhe-Min coastal current dominates the inshore area associated with a deepening of the mixed layer. When the winter monsoon is weakened or the southwesterly wind prevails, the northeastward TWC dominates in the inshore area.

The missing link: tidal‐influenced activity a likely candidate to close the migration triangle in brown shrimp C rangon crangon ( C rustacea, D ecapoda) - Marc Hufnagl; Axel Temming; Thomas Pohlmann (Fisheries Oceanography, 2014)
Life cycle closure for species inhabiting areas with daily varying currents but directed net water transport requires specific behavior to minimize losses due to advection of passive drifting life stages. Variations in swimming activity of different‐sized C rangon crangon (15–65 mm total length) were therefore monitored under constant laboratory conditions immediately after being caught in the G erman W adden S ea. Activity of shrimps of different sizes, caught at different seasons, always peaked at times corresponding with ebb tide in the habitat from where they were taken. This behavior was maintained for several days if no external stimuli were present but shifted to night activity if a light–dark cycle was provided. The observed behavior/activity pattern was included in a coupled hydrodynamic and individual‐based model ( IBM ) and the shift in the location of a shrimp cohort was monitored over time. Performance of ebb tide activity not only allowed the shrimps to reach the preferred deeper winter and spawning areas but also allowed them to migrate against the dominating current from eastern nurseries to more western located spawning areas. Passively drifting larvae released at these locations and later larval and juvenile stages that perform flood tide transport can reach the nurseries again. This links the nurseries and adult spawning grounds and closes the migration triangle.

Assimilation of surface currents into a regional model over Qingdao coastal waters of China - Jian Zhao; Xueen Chen; Jiangling Xu; Wei Hu; Jinrui Chen; Thomas Pohlmann (Acta Oceanologica Sinica, 2013)

Simulation and detection of tsunami signatures in ocean surface currents measured by HF radar - Klaus-Werner Gurgel; Anna Dzvonkovskaya; Thomas Pohlmann; Thomas Schlick; Eric Gill (Ocean Dynamics, 2011)

The influence of the Three-Gorges Dam on hydrographic and hydrodynamic conditions of the East China Sea - Xiaopeng Fan; Feng Zhou; Xueen Chen; Daji Huang; Thomas Pohlmann (Acta Oceanologica Sinica, 2011)

The influence of meteorological variation on the upwelling system off eastern Hainan during summer 2007–2008 - Jian Su; Jun Wang; Thomas Pohlmann; Dongfeng Xu (Ocean Dynamics, 2011)

A novel high resolution model without open boundary conditions applied to the China Seas: first investigation on tides - Huaming Yu; Xueen Chen; Xianwen Bao; Pohlmann Thomas; Dexing Wu (Acta Oceanologica Sinica, 2010)

A seasonally resolved bottom‐water temperature record for the period AD 1866–2002 based on shells of Arctica islandica (Mollusca, North Sea) - Bernd R. Schöne; Miriam Pfeiffer; Thomas Pohlmann; Frank Siegismund (International Journal of Climatology, 2005)
Existing studies on recent global warming are almost exclusively based on environmental data from the Earth's surface. Seasonal information on the effects of climate change on subsurface settings of mid to high latitudes is extremely scarce. Here, we present the first temperature proxy record from bottom (c. 50 m) water settings of the North Sea employing the oxygen isotope composition of ocean quahog shells. Results indicate that δ 18 O aragonite measured across shells of Arctica islandica can provide reliable estimates (±0.25 to ±0.4 °C) of the ambient bottom water temperatures. Over the period AD 1880–2001, warming trends in bottom waters are of the order of 0.042 to 0.138 °C/decade. Apparently, the annual maximum‐temperature trend shows a twofold increase over the past four decades (0.236 °C/decade) while the minimum‐temperature trend has remained relatively stable (0.042 °C/decade). During the same time interval, however, annual maximum temperatures at the sea surface quadrupled. Shell oxygen‐isotope‐derived winter temperatures also provide a proxy for the winter North Atlantic oscillation index (WNAO). Some 28 to 50% of the variability in minimum temperatures below the thermocline can be explained by changes of the WNAO. Our new tool enables testing and verification of climate models prior to the 20th century greenhouse forcing. Copyright © 2005 Royal Meteorological Society

Comparison between measured and calculated tidal ellipses in the German Bight - Noel Carbajal; Thomas Pohlmann (Ocean Dynamics, 2004)

Simulating the temporal and spatial dynamics of the North Sea using the new model GETM (general estuarine transport model) - Adolf Stips; Karsten Bolding; Thomas Pohlmann; Hans Burchard (Ocean Dynamics, 2004)

The South China Sea warm-core ring 94S and its influence on the distribution of chemical tracers - Li Li; Thomas Pohlmann (Ocean Dynamics, 2002)

Suspended particulate matter in the Southern North Sea: Application of a numerical model to extend NERC North Sea project data interpretation - Walter Puls; Thomas Pohlmann; Jürgen Sündermann (Ocean Dynamics, 1997)

Estimating the influence of advection during FLEX’76 by means of a three- dimensional shelf sea circulation model - Thomas Pohlmann (Ocean Dynamics, 1997)